PENYULUHAN KESIAPSIAGAAN BENCANA KEBAKARAN DI DESA LERENG KECAMATAN KUOK - Lira Mufti Azzahri Isnaeni; Etri Gustriana (Universitas Pahlawan Tuanku Tambusai, 2022)
Fire is one type of disaster that is quite potential to leave large losses if it does not get sufficient attention and handling in disaster mitigation efforts. Many people still do not understand the concept of disaster preparedness in tackling the bad impacts caused by disasters. counseling on disaster preparedness to heads of families in Lereng village, district. Kuok. Which can be identified in several specific problems, namely whether there is an impact of disaster preparedness counseling on increasing the knowledge of family heads in Lereng village, Kec. Kuok. However, after participating in community outreach activities, they will be able to understand the meaning of disaster, factors causing fire disasters, disaster preparedness, activities in disaster preparedness and benefits in preparedness. This community service activity aims to grow and increase community knowledge, especially family heads related to fire disaster preparedness that is at risk of occurring in slope villages, Kec. Kuok. This activity will be carried out using several methods, namely lectures and questions and answers. Participants in this service activity are community heads of 35 people. Regarding the problems faced by partners, the lecturer as the executor of community service (PKM) together with 3 students will provide a solution to overcome the problem of high losses caused by the fire disaster. Keywords : fire ; education